FACTORS AFFECTING CONSUMERS’ CHOICE IN RESIDENTIAL PROPERTIES AND THE FUTURE OF THE REAL ESTATE BUSINESS IN THE PHILIPPINES - Jose Mari M. Lee; Eduardo G. Ong, PhD, DPA, DBA (International Journal of Accounting, Finance and Business, 2020)
Today, marketers are customer-oriented and the ultimate concern is to identify the consumers' decision-making process. The study was based on Theory of Reasoned Action and Theory of Planned Behavior. The research design is quantitative method. Descriptive-Exploratory Design was utilized in the study. The respondents were 400 potential residential property buyers. This study was limited to the following criterion: respondents must be 18 years old and above; respondents must have work; and, respondents must have plans to buy residential property from any of the top 10 real estate developers in the Philippines. The researcher used purposive sampling method. The data collected through survey questionnaires was entered and analyzed using SPSS software. The study examined the significant relationship between the factors affecting a purchase namely cultural, social, personal, and psychological factors and consumers’ choice such as price, location, safety and security, facilities and amenities, and exclusivity towards purchase intention of residential property. Based on the findings of the study, the researcher proposed a model for the consumer behavior of residential properties in the Philippines.